2016
DOI: 10.1142/s1088424616500838
|View full text |Cite
|
Sign up to set email alerts
|

Optical, electrochemical and third-order nonlinear optical studies of triphenylamine substituted zinc phthalocyanine

Abstract: Zinc phthalocyanine possessing triphenylamine at its peripheral position has been synthesized and its optical, emission, electrochemical and third-order nonlinear optical (NLO) properties were investigated. Soret band was broadened due to the presence of triphenylamine moiety. Electrochemical properties indicated that both oxidation and reduction processes were ring centered. Emission spectra were recorded in different solvents and the fluorescence yields obtained were in the range of 0.02–0.17 while the time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…We further compared the NLO coefficients of our phthalocyanine moieties with several recently reported molecules (different phthalocyanine derivatives) obtained with femtosecond pulses (similar to the experimental conditions used in the present study), and the results are summarized in Table . Our molecules demonstrated excellent NLO properties, which were on par to the coefficients in studies conducted by other groups in the MHz regime ,,,,, and in the kHz regime. , When compared to the results published by other groups our molecules demonstrated superior NLO behavior as compared to their materials. Venkatram et al reported β values of 10 –12 cm/W at 800 nm (kHz pulses) for alkoxy phthalocyanines obtained using femtosecond Z -scan experiments.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…We further compared the NLO coefficients of our phthalocyanine moieties with several recently reported molecules (different phthalocyanine derivatives) obtained with femtosecond pulses (similar to the experimental conditions used in the present study), and the results are summarized in Table . Our molecules demonstrated excellent NLO properties, which were on par to the coefficients in studies conducted by other groups in the MHz regime ,,,,, and in the kHz regime. , When compared to the results published by other groups our molecules demonstrated superior NLO behavior as compared to their materials. Venkatram et al reported β values of 10 –12 cm/W at 800 nm (kHz pulses) for alkoxy phthalocyanines obtained using femtosecond Z -scan experiments.…”
Section: Resultssupporting
confidence: 73%
“…Over the last several years, our group was actively involved in designing quite a few novel phthalocyanines and/or similar molecules along with their metallic derivatives by introducing substituents either at peripheral or nonperipheral positions, and we investigated their third-order NLO properties and excited state dynamics. Previous reports and their detailed studies suggest that it is indispensable to introduce functional groups at peripheral positions of phthalocyanine that are suitable for various optoelectronic applications. To achieve the strong NLO coefficients, we have designed and synthesized two carbazole-substituted phthalocyanines in which the carbazole moiety is tethered to phthalocyanine by using two different positions of the carbazole, i.e., carbazole ring substituted (9-phenyl-9 H -carbazol-2-yl) ( CBZPC1 ) and N -phenyl substituted (4-(9 H -carbazol-9-yl)­phenyl) ( CBZPC2 ) phthalocyanines (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the NLO properties with 2 ps, 1 kHz pulse and 150 fs, 80 MHz pulse at 800 nm. 41 With fs pulses, the molecule demonstrated 2PA absorption with a coefficient of 10 À7 cm W À1 and self-defocusing with n 2 being $10 À12 cm 2 W À1 while ps pulses demonstrated a 2PA absorption coefficient of 10 À11 cm W À1 and self-defocusing with n 2 of $10 À14 cm 2 W À1 . Very recently Bhattacharya et al 47 have reported the usage of carboxyl group at the peripheral position of ZnPc to synthesize novel phthalocyanines (CBZPc1 and CBZPc2) and investigated their optical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 96%
“…[29][30][31][32][33][34][35] In this regard, our group has also investigated many phthalocyanines to understand the structure and NLO properties correlation for identifying potential molecules for various photonic applications. [36][37][38][39][40][41][42][43][44][45][46][47] over the last few years. To this end our group has been involved in investigating and optimizing the NLO properties of different phthalocyanine, Corrole 37 molecules in the form of thin lms, nanoparticles (NPs) and solutions.…”
Section: Introductionmentioning
confidence: 99%